Role of Maternity Benefits in Increasing Female Workforce Participation and Economic Growth in India - Paromita Mukherjee; Dr. Sanchita Saha (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The low rate of female labour force participation in India, in spite of progressive laws aimed at improving maternity benefits, presents serious obstacles to economic development. Using secondary data from the Periodic Labour Force Survey (PLFS) and the National Sample Survey Office (NSSO), this research examines the effects of maternity benefits on female employment participation and economic development in India. This study uses both descriptive and economic analytic methods to investigate the relationship between female labour force participation and maternity benefits. Important results show that better maternity benefits are favourably correlated with more women entering the workforce, which boosts economic development overall. The research highlights the areas that need development and the success of present strategies by revealing demographic and socioeconomic variables impacting this connection. The study's findings indicate that by raising labour market participation rates, comprehensive maternity benefits not only assist working moms but also promote economic growth. It is recommended that policymakers take these results into account when formulating initiatives to improve the integration of women into the workforce.